THE IMPORTANCE OF SOCIAL-Emotional Intelligence in Developing Social Competence in Students (Universal International Scientific Journal, 2026)
This article sheds light on the role of socio-emotional intelligence in the process of forming and developing social activity in students of higher educational institutions from a scientific and practical perspective. The components of socio-emotional intelligence, their importance in personal development and social life, and their impact on students' activity in social relations are analyzed. It also substantiates the possibilities of forming important social skills in students, such as leadership, responsibility, teamwork, and constructive problem solving, through the development of socio-emotional intelligence.
Keywords: social engagement; social-emotional intelligence; student